2016
DOI: 10.5713/ajas.16.0351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size of processed barley grain, enzyme addition and microwave treatment on in vitro disappearance and gas production for feedlot cattle

Abstract: ObjectiveThe effects of particle size of processed barley grain, enzyme addition and microwave treatment on in vitro dry matter (DM) disappearance (DMD), gas production and fermentation pH were investigated for feedlot cattle.MethodsRumen fluid from four fistulated feedlot cattle fed a diet of 860 dry-rolled barley grain, 90 maize silage and 50 supplement g/kg DM was used as inoculum in 3 batch culture in vitro studies. In Experiment 1, dry-rolled barley and barley ground through a 1-, 2-, or 4-mm screen were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Tables 2 and 3 shows the results of the IVSD and gas production experiments. Overall, the 7hIVSD and kd starch decreased (P < 0.05) as the mPS increased, in agreement with previous studies performed in vitro (Hoffman et al, 2012;Tagawa et al, 2017) and in vivo (San Emeterio et al, 2000;Callison et al, 2001). In particular, the 7hIVSD values decreased linearly with mPS (P < 0.05) in corn, barley, wheat, rye, pea, and faba feeds, and quadratically (P < 0.05) for the other feeds (Figure 1).…”
Section: Short Communicationsupporting
confidence: 90%
See 1 more Smart Citation
“…Tables 2 and 3 shows the results of the IVSD and gas production experiments. Overall, the 7hIVSD and kd starch decreased (P < 0.05) as the mPS increased, in agreement with previous studies performed in vitro (Hoffman et al, 2012;Tagawa et al, 2017) and in vivo (San Emeterio et al, 2000;Callison et al, 2001). In particular, the 7hIVSD values decreased linearly with mPS (P < 0.05) in corn, barley, wheat, rye, pea, and faba feeds, and quadratically (P < 0.05) for the other feeds (Figure 1).…”
Section: Short Communicationsupporting
confidence: 90%
“…Thus, Patton et al (2012) declared "…inaccuracies in prediction of starch degradability in the rumen may be mainly due to processing effects and particle sizes, but these were not well reported in literature and were difficult to estimate," and Moharrery et al (2014) stated "…effects of physical structure and heat treatment were initially tested, however data balance did not allow for conclusive statements for the present dataset and approach." Previous studies suggested that the mean particle size (mPS) of feeds can affect digestion rate (Hoffman et al, 2012;Zhao et al, 2015;Tagawa et al, 2017), and that differences in the passage rates of large, medium, and small particles exist within the different gastrointestinal compartments of ruminant animals (Nocek and Tamminga, 1991;Offner and Sauvant, 2004;Ferraretto et al, 2013). We previously modeled the effects of mPS on in vitro rumen starch degradation (IVSD) and OM fermentability (Gallo et al, 2016) by examination of a wide range of mPS, with meals consisting of dry wholekernel corn (n = 11 mPS, 0.46 to 3.50 mm) and dry hulless whole-kernel barley (n = 10 mPS, 0.11 to 2.98 mm), by use of well-established rumen-based in vitro methods.…”
Section: Short Communicationmentioning
confidence: 99%
“…Additionally, the high number of cross-links within plant cell wall carbohydrates and lignin through the growing season decrease digestibility and bounds the utilization of forages by ruminants. Consequently, it will demand several cellulolytic enzymes to degenerate these materials effectively [ 6 , 7 , 8 ]. As an outcome, many strategies have been exploited to enhance fiber degradation in the rumen.…”
Section: Introductionmentioning
confidence: 99%
“…Whole grain forage is poorly digested by farm animals (Dehghan‐Banadaky, Corbett, & Oba, 2007; Saleem et al, 2020). To increase digestibility and nutritional value, forage is pretreated with various methods (Humer & Zebeli, 2017; Shirmohammadi et al, 2020; Tagawa, Holtshausen, McAllister, Yang, & Beauchemin, 2017). The traditional mechanical grinding of grain is the most widely known and ancient technology (Acar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%